2015
DOI: 10.1111/aor.12635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interaction Between Ventricular Assist Device Assistance and Autoregulated Mock Circulation Including Frank–Starling Mechanism and Baroreflex

Abstract: A mock heart circulation loop (MHCL) is a hydraulic model simulating the human circulatory system. It allows in vitro investigations of the interaction between cardiac assist devices and the human circulatory system. In this study, a preload sensitive MHCL, the MHCL , was developed to investigate the interaction between the left ventricle and left ventricular assist devices (LVADs). The Frank-Starling mechanism was modeled by regulating the stroke volume (SV) based on the measured mean diastolic left atrial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This system allows reproducing the Frank‐Starling autoregulation mechanism of the heart, which regulates the cardiac output depending on the ventricle preload parameter that can be expressed as end‐diastolic pressure (EDP), end‐diastolic volume (EDV), or mean left atrial pressure like in Ref. .…”
Section: Methodsmentioning
confidence: 99%
“…This system allows reproducing the Frank‐Starling autoregulation mechanism of the heart, which regulates the cardiac output depending on the ventricle preload parameter that can be expressed as end‐diastolic pressure (EDP), end‐diastolic volume (EDV), or mean left atrial pressure like in Ref. .…”
Section: Methodsmentioning
confidence: 99%
“…For this study the preload (Frank-Starling mechanism) and afterload (autonomic nervous system) sensitivity of the ventricles were not modelled in the SCVL. Preload and afterload sensitive motors have been implemented into other cardiovascular simulators [25,26,28]. Implementation of these features in the SCVL is necessary to give a more comprehensive understanding of the hemodynamic effects of an RBP device in the DA.…”
Section: Limitationsmentioning
confidence: 99%
“…In recent years, much progress has been made in the design and development of cardiovascular simulators with close similarity to a native system for research and training [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…1 [12, 21, 30, 38]. However, for the purpose of repeatability within a MCS, the culmination of this knowledge can be summarized by simplifying the performance of the LV through three principal factors: preload, afterload, and contractility [24, 25]. These have significant implications on VAD performance [39].…”
Section: Introductionmentioning
confidence: 99%
“…Their research concluded that the elastance-based model performed more realistically when reproducing specific cardiovascular scenarios and that many MCS designs could be considered inadequate, if careful consideration is not made to the pumping action of the ventricle. Subsequent in vitro testing utilizing this control approach successfully reproduced an elastance mechanism of a natural ventricle by mimicking preload and afterload sensitivity [25]. Preload was modified by means of manually changing the fluid content of the closed loop hydraulic circuit, while afterload was varied by increasing or decreasing the systemic arterial resistance within a modified Windkessel model.…”
Section: Introductionmentioning
confidence: 99%